Death and Tenses : Posthumous Presence in Early Modern France - Kenny, Neil (New York Oxford University Press, 2015)
Death and Tenses explores the question of what tense we should use to refer to the dead. Focusing on sixteenth- and early seventeenth-century texts in French and Latin, it compares early modern examples with modern French and English, asking whether changes in more recent beliefs in posthumous survival have led to different tense usage.
Include Illustrations, Bibliography and Index
Keywords: Death in literature -- French literature -- Latin literature, Medieval and modern -- Grammar, Comparative and general--Tense